2006
DOI: 10.1007/s00431-006-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of procalcitonin concentrations as a diagnostic marker of the PFAPA syndrome

Abstract: PFAPA syndrome is a clinical entity of unknown etiology characterized by periodic episodes of high fever accompanied by aphthous stomatitis, pharyngitis/tonsillitis, and cervical adenitis [3,5]. Since specific laboratory abnormalities for the PFAPA syndrome are inexistent, it is usually diagnosed clinically after excluding other probable causes of the fever, such as infection [1]. In PFAPA patients, discriminating between a fever attack due to bacterial infection and a fever attack due to noninfectious inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 5 publications
1
31
1
1
Order By: Relevance
“…Serum immunoglobulin (Ig) levels are normal, IgD is normal or slightly elevated (20,23). All inflammatory parameters return to normal between the attacks (22).…”
Section: Laboratory Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Serum immunoglobulin (Ig) levels are normal, IgD is normal or slightly elevated (20,23). All inflammatory parameters return to normal between the attacks (22).…”
Section: Laboratory Findingsmentioning
confidence: 89%
“…C-reactive protein (CRP) is high at the beginning of the attack, sedimentation may (20). Procalcitonin does not increase like other acute phase reactants (22). Serum immunoglobulin (Ig) levels are normal, IgD is normal or slightly elevated (20,23).…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Yoshihara et al found that levels of CRP were moderately elevated while PCT was normal during febrile attacks in children with PFAPA (10) . In our study, while PCT values were found to be within normal limits during the fever attacks in the study group, they were significantly increased in the control group.…”
Section: Dıscussıonmentioning
confidence: 99%
“…Lastly, CXCL10 was shown to be elevated during febrile episodes of PFAPA but not during other periodic fever syndromes or infectious conditions (6) . CRP and PCT proved to be promising in the diagnosis of PFAPA in some studies (7)(8)(9)(10) . A limited number of studies exist where CRP and PCT have been evaluated together to diagnose this syndrome.…”
Section: ıNtroductıonmentioning
confidence: 99%
“…During febrile attacks, patients present elevation of white blood cells, with preponderance of neutrophils and of acute phase reactants. Procalcitonin has normal values during fl ares and this fi nding can exclude bacterial infection (9,10). Between attacks, all infl ammatory parameters are normal.…”
Section: Introductionmentioning
confidence: 94%